Measurement report: The ice-nucleating activity of lichen sampled in a northern European boreal forest - U. Proske; U. Proske; U. Proske; M. P. Adams; G. C. E. Porter; M. A. Holden; M. A. Holden; J. Bäck; B. J. Murray (Atmospheric Chemistry and Physics)
Ice-nucleating particles (INPs) facilitate the heterogeneous freezing of cloud droplets and thus modify cloud properties. Hence, it is important to understand the sources of INPs. During the HyICE-2018 campaign, which took place in the boreal forest of Hyytiälä, substantial concentrations of airborne heat-sensitive biological INPs were observed, despite many potential biological sources of INPs being snow-covered. A potential source of INPs that were not covered in snow was lichens that grow on trees; hence, we investigated these lichens as a potential source of biological INPs in this boreal forest environment. INPs derived from lichen sampled during HyICE-2018 are shown to nucleate ice at temperatures as warm as −5 °C with 103 INPs per gram of lichen. Successive filtration to smaller sizes removes some of the most active INPs in suspension, but substantial activity remains, even when filtering to 0.1 µm. The small size of the INPs from lichen means they have the potential to either be emitted directly into the atmosphere or be associated with larger particles, such as lichenous reproductive aerosol types (spores or diaspores). We also show that the INPs from lichens from Hyytiälä are sensitive to heat, which is similar to the INPs sampled from the atmosphere of Hyytiälä and consistent with the presence of ice-active proteins. Adding to previous evidence of lichenous INPs, this study shows that lichens from a European boreal forest in Hyytiälä harbour INPs. This novel finding may be especially important in this snow-covered habitat where few, if any, other biological INP sources are available. The great terrestrial abundance of lichens in Hyytiälä, and around the world, calls for further research to combine their ice-nucleating ability with dispersal studies to evaluate the flux of lichenous INPs into the atmosphere, as well as to what extent these particles reach heights and locations where they might influence cloud properties.